Sugarcane cystatin CaneCPI-1 promotes osteogenic differentiation in human dental pulp cells: a new insight into cysteine proteases inhibitors - Rodrigues, E. M. [UNESP]; Viola, K. S. [UNESP]; Gomes-Cornelio, A. L. [UNESP]; Soares-Costa, A.; Henrique-Silva, F.; Rossa-Junior, C. [UNESP]; Guerreiro-Tanomaru, J. M. [UNESP]; Tanomaru-Filho, M. [UNESP] (Wiley-Blackwell, 2020)
Aim To investigate the biocompatibility, type of cell death, osteogenic bioactivity and mRNA expression of the osteogenic markers, induced by CaneCPI-1 in human dental pulp cells (hDPCs). Methodology hDPCs exposed to CaneCPI-1 and not exposed (control) were evaluated for cell viability by the 3-(4,5-dimethylthiazol)-2,5-diphenyltetrazolium bromide (MTT) assay; apoptosis by flow cytometry; alkaline phosphatase (ALP) activity by calculation of thymolphthalein release; gene expression of bone morphogenetic protein 2 (BMP-2), runt-related transcription factor 2 (RUNX2), ALP, osteocalcin (OC), bone sialoprotein (BSP) by qPCR; and mineralized nodules production by using alizarin red staining. The data were analysed by one-way analysis of variance (anova) and Turkey's post-test, two-wayanovaand Bonferroni post-test or t-test (P < 0.05). Results CaneCPI-1 induced no apoptosis and had no cytotoxic effect, except in the concentration of 33.20 mu m, in which cell viability was significantly lower than the control (alpha-MEM nonosteogenic medium serum-free) (P < 0.05). There was significantly greater ALP activity, greater expression of the BMP-2, RUNX2, ALP, OC and BSP genes and greater mineralized nodules production in the CaneCPI-1 group in comparison with the control or osteogenic alpha-MEM control (alpha-MEM osteogenic medium - L-ascorbic acid and beta-glycerophosphate) (P < 0.05). Conclusions CaneCPI-1 was cytocompatible and also induced the differentiation of hDPCs in osteogenic phenotypein vitro. CaneCPI-1 is a promising molecule to induce pulp repair.
Keywords: canecystatin; cell differentiation; cysteine proteinase inhibitor; human dental pulp cells